2013
DOI: 10.4049/jimmunol.1203546
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and Therapeutic Effects of Adenanthin on Experimental Autoimmune Encephalomyelitis by Inhibiting NF-κB Signaling

Abstract: MaterialSupplementary http://www.jimmunol.org/content/suppl/2013/08/23/191.5.2115.DC1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Also, although Prxs were the only adenanthinͲbinding proteins detected with leukemic cells [1] this group observed interaction with components of the NFNB signaling pathway in their model of autoimmune encephalomyelitis [2].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Also, although Prxs were the only adenanthinͲbinding proteins detected with leukemic cells [1] this group observed interaction with components of the NFNB signaling pathway in their model of autoimmune encephalomyelitis [2].…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, the finding that Prxs did not appear to be the target in the encephalitis model [2] implies that adenanthin may not be as selective as initially proposed. In order to understand more about the biological activity of adenanthin, we have compared its reactivity with Prxs, GSH and components of the reductive pathways involved in Prx and GSH recycling.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…25 Hence, ADNT has arisen as a fairly potent research tool for interfering with thioldependent peroxidases. Because ADNT has been proposed to be a potential immunomodulatory 27 or anti-tumour compound, 27,28 it becomes important to identify the full spectrum of pharmacological actions of ADNT in biological systems, particularly those related to tumour surveillance. In this study, we assessed the effects of ADNT on the functions of primary human NK cells.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…However, the possibility could not be excluded that adenanthin might also bind with other protein(s). Actually, we showed that adenanthin exerts effective preventive and therapeutic effects on experimental autoimmune encephalomyelitis, which might be mediated via its inhibitory action on NF-B signaling pathway [43]. More recently, it was also shown that, next to Prx I/II, adenanthin also targets and inhibits the activity of additional proteins including the thioredoxin-thioredoxin reductase (TrxR) system and protein disulfide isomerase [44], as well as glutathione (GSH) [45].…”
Section: Adenanthinmentioning
confidence: 99%